Morphological and Chemical Analysis of Different Types of Calcium Silicate-Based Cements - Okba Mahmoud; Nashwan Abdullah Al-Afifi; Mohideen Salihu Farook; Maysara Adnan Ibrahim; Saaid Al Shehadat; Mohammed Amjed Alsaegh (International Journal of Dentistry)
Objectives. Particle size and shape can influence the properties of materials. However, to improve the physicochemical and biological properties of mineral trioxide aggregate (MTA), silicate-based hydraulic cements were introduced. This study aimed to evaluate and compare the major constituents and crystalline structures along with the surface morphology of different types of calcium silicate-based cement (CSC). Materials and Methods. Six different types of CSC (white Portland cement, white ProRoot MTA, white MTA Angelus, Biodentine, and Endosequence, both putty and paste) were used in this study. Five samples of each material were analyzed in both uncured and cured cement using scanning electron microscopy/energy-dispersive X-ray (SEM/EDX), X-ray diffraction (XRD), and Fourier transform-infrared spectroscopy (FTIR). Results. SEM analysis showed that the surfaces of all materials consisted of particle sizes ranging from 0.194 μm to approximately 51.82 μm. The basic elements found in both uncured and cured cement of all tested materials using EDX were carbon, calcium, silicon, and oxygen. A difference was observed in the presence or absence of magnesium, aluminum, bismuth, zirconium, and tantalum. XRD showed that all tested materials were composed mainly of tricalcium silicate and dicalcium silicate, which are the main components of Portland cement. FTIR analysis showed aromatic rings, phosphine PH, alkyl halides, and alcohol O-H groups in all tested materials but at different wavenumbers. Conclusions. The different types of CSCs tested in this study were primarily modified types of Portland cement with the addition of radiopacifiers. ProRoot MTA and MTA Angelus contained bismuth oxide, Biodentine contains zirconium oxide, whereas Endosequence root repair materials (both putty and paste) contained zirconium oxide and tantalum oxide. Endosequence root repair materials showed smaller particle sizes than the other groups. White PC had the most irregular and large particle sizes. CSC had a smaller particle size, except for MTA Angelus. Clinical Relevance. The composition of CSC has a direct influence on the properties of these cements, which may affect the clinical outcome of the treatment.